Informal employment: What is missing from national economic recovery plans? - Siviwe Mhlana; Rachel Moussié; Sally Roever; Michael Rogan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Throughout 2021, fiscal stimulus packages were introduced to jump-start the COVID-19 'post-pandemic' economic recovery process. While calls for economic recovery packages that promise to 'build back better' have come from many directions, the under-allocation of recovery resources directed at workers in the informal economy threatens the recovery of livelihoods for the majority of the world's workforce. This paper analyses the economic recovery approaches of two low-income (Bangladesh and Kenya) and two middle-income (South Africa and Thailand) countries. The paper assesses the economic recovery responses in light of what is known about the impact of the crisis on informal workers globally, and the structure of informal employment in each country. The paper assesses national recovery packages with particular attention to the largest segments of informal employment and those where women are over-represented. The paper concludes with a reflection on what more needs to be done to ensure that national level economic recovery packages can support the livelihoods of the majority of workers in emerging and developing countries.
Keywords: E26; E60; E62; E65; 330; COVID-19; economic recovery; informal economy